Effects of Fasting on Body Weight, Serum Glucose and Creatinine and Histotexture of Liver and Kidney in Swiss Albino Mice - Saha, Tithe; Sujan, Khaled Mahmud; Haque, Ziaul; Islam, Md Kamrul (Research in Agriculture Livestock and Fisheries, 2020)
Fasting means remaining without foods and water from a specific period of time which is important for improving health and increasing longevity. The present study was conducted to investigate the effect of fasting on body weight, serum biochemistry and histomorphological changes of liver and kidney in mice. A total of 18 Swiss Albino Mice (Musmusculus), 28-35 days old with an average body weight of 26.2 ± 1 gm were randomly divided into three groups. Group A was considered as control (n=6) and fed on standard mice pellet and fresh drinking water. Group B was considered as 14 hours fasting group (n=6), kept fasting for 14 hrs and Group C was considered as 18 hours fasting group (n=6), kept fasting for 18 hrs. At the end of the experiment, blood and tissues were collected for biochemical and histomorphological examination. Data showed that no significant change was found in body weight, serum glucose and creatinine level in fasting groups Histopathological studies of liver and kidney revealed that fasting could initiate minor change in the normal structures of liver but no architectural change in kidney. Slight depletion of glycogen was found in hepatocytes of liver. From the present study it can be concluded that fasting may be beneficial as its decreases body weight gain and have not any significant alteration in the liver and kidney histotextures. Res. Agric., Livest. Fish.7(3): 421-430, December 2020